Soil-plant relationship in Calluna heathlands after experimental burning and nitrogen fertilization, studies from NW Spain - Marcos, Elena; Taboada, Angela; Calvo, Leonor (Ecological Questions, 2015)
We studied changes in the relationship between soil nutrient content and plant species richness in Calluna heathlands after seven years of experimental burning (B) and nitrogen fertilization (NF). Our results indicate that both the treatments (B, NF, B+NF) and modification of several soil characteristics (total N, available Na, and C:N ratio) reflected in a significant increase in plant species richness.